Salvage Chemotherapy in Recurrent Cervical Cancer With Biweekly Pegylated Liposomal Doxorubicin (Lipo-Dox) - Jen-Ruei Chen; Yuh-Cheng Yang; Tze-Chien Chen; Jerry Cheng-Yen Lai; Shing-Jyh Chang; Chi-Long Chang; Kung-Liahng Wang (Elsevier, 2008)
Objective: To investigate the objective response rate to and tolerance of biweekly Lipo-Dox (TTY Biopharm Co. Ltd., Taipei, Taiwan) at a dosage of 20 mg/m2 in previously treated patients with recurrent cervical cancer. Materials and Methods: This study was performed as a Simon's two-stage phase II clinical trial. Ten patients with recurrent cervical cancer were enrolled between April 2003 and December 2005 at the Mackay Memorial Hospital. Lipo-Dox (20 mg/m2 intravenous) diluted in 250 mL of 5% dextrose solution was administered at 2-weekly intervals. Results: The mean age of the patients was 51 ± 11.1 years. The mean number of cycles of Lipo-Dox injection was 4.6 (range, 1-12 cycles). Nine patients (90%) had disease progression. Only one patient (10%) achieved a partial response, and this was also the only patient who experienced WHO grade 2 palmar-plantar erythrodysesthesia, which led to treatment delay for 2 months. The median survival time was 2 months (range, 2-6 months). The majority of patients experienced grade 1 or 2 anemia (30%), leukopenia (20%) or thrombocytopenia (20%), and others exhibited symptoms of nausea and vomiting (30%). Conclusion: Salvage chemotherapy with Lipo-Dox at a dose of 20 mg/m2 administered at 2-weekly intervals produced limited responses in patients with recurrent cervical cancer. This trial will not proceed to the second stage. These results may discourage the management of recurrent cervical cancer with single-agent Lipo-Dox in future clinical trials.